Knowledge Capture Menggunakan Teknik Explore, Elaborate dan Execute Untuk Bagian Kesiswaan Sekolah - Victor Peter Lodewyk Duan; Danny Manongga; Ade Iriani (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
Students are late to school showed a lack of awareness about discipline. The teachers who handle the student late are created the tacit knowledge. This paper applied explore, elaborate and execute technique to capture the knowledge. The purpose is to documenting and stored it as a wealth of school knowledge by create a model in knowledge capture. The model of knowledge capture can be an indicator in capturing and documenting knowledge process so it will be good impact when handling the students late. The result showed the model of knowledge capture was created based on three step explore, elaborate and execute with the factors who cause students late. The use of technology have not technofull applicable in process to capturing knowledge except in documenting and storage process, allow to presence a utilization technology design in capturing knowledge on future research.